Strategi Bertahan UMKM Es Teh Jumbo di Kota Palembang - Khusnul Ari Nugroho; Paturahman Aditia; Fairuz Nadhif Abryant; Anugerah Hafiz Reval Hidayat; Anggreany Husia (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
MSMEs are an important sector in the local economy, including in the city of silaberanti (PALEMBANG), particularly in the ready to drink beverage business, which is facing fierce competition and market trends. These conditions require MSMEs to have survival strategies in order to continue operating their businesses. This study aims to determine the survival strategies implemented by jumbo iced tea MSMEs and the factors that influence business resilience and customer loyalty. This study uses a qualitative approach. Data collection was conducted through in depth interviews and direct observation with business owners. The results of this study indicate that the resilience of jumbo iced tea MSMEs is influenced by consistent product quality, affordable and stable pricing, friendly service, and the ability of business owners to adapt to market conditions. In addition, the religious values held by business owners can play a role in shaping business resilience and calmness in making business decisions. These strategies are able to maintain customer trust and loyalty, so that the business continues to run and survive amid increasingly fierce competition. This study is expected to be a reference for other MSME entrepreneurs in designing sustainable business resilience strategies.